Production of Effective Microorganisms (Em) From Organic Waste from Traditional Markets in Tambelang District as Biocatalysts - Novi Laura Indrayani; Riri Sadiana (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2021)
Municipal solid waste largely consists of market waste which has become a critical problem for city environment. Indiscriminate dumping of waste around city poses environmental hazards causing ecological imbalances with respect to land, water and air pollution. This waste in the form of vegetable left over, rotten vegetables can be successfully being converted into effective micro-organism i.e. In the present work, the influence of hydraulic retention time on dark fermentation metabolism was evaluated through the operation and analysis of a series of three tank reactors ranging from 7 dayto 21 day.In depth analysis of microbial communities showed growth increases up to 8,0 x 108cpu/ml.